Knowledge, behaviors and opinions of medical faculty students during the COVID-19 pandemic - Alanya Tosun, Sebnem; Nomer, Kaan; Alemdaroglu, Sila; Ozkaya, Enis (Annals of Medical Research, 2021)
Aim: The emergency of COVID-19 pandemic has severely affected medical students’ education and the possibility of being considered as health-care professionals has come to mind. We described knowledge, behaviours and opinions of medical students during the pandemic and separated into the continents and compared them with our country. Materials and Methods: The cross-sectional worldwide study including 26 items online questionnaire was conducted between March 24th and April 9th, 2020.Medical students were grouped according to their continent and Turkey as a separate group. Results: 1454 medical students studying in 64 countries from 4 continents including Asia, Europe, South America and Africa participated in study. Only 23.7% of all was adequately informed about approach to outbreak situations. This was the lowest in Europe and followed by Turkey (20.8%, 21.7% respectively).71.2% of all changed their hygiene habits; paying attention to social distance increased from 2% to 61.9%. In Africa, 58.6% of students feel qualified to work in hospitals voluntarily, whereas it was only 19.9% in Turkey and 29.2% in Europe (p0.001).91.5% of Asian and 87.7% of European students would agree to volunteer in hospitals. In Turkey it was only 71.1% (p0.001).75.9% of all support the view that they should be qualified to volunteer in hospitals when necessary. Conclusion: Medical students seem to want to volunteer, but have not been adequately informed about the approach to outbreak situations. An international consensus on medical students’ roles may improve medical school programs about the current COVID-19 Pandemic and future ones.
Keywords: COVID-19 pandemic; education medical; surveys and questionnaires